Sol-Gel Synthesis of Non-Silica Monolithic Materials - Bartłomiej Gaweł (Materials, 2010)
Monolithic materials have become very popular because of various applications, especially within chromatography and catalysis. Large surface areas and multimodal porosities are great advantages for these applications. New sol-gel preparation methods utilizing phase separation or nanocasting have opened the possibility for preparing materials of other oxides than silica. In this review, we present different synthesis methods for inorganic, non-silica monolithic materials. Some examples of application of the materials are also included.